A novel DCX missense mutation in a family with X-linked lissencephaly and subcortical band heterotopia syndrome inherited from a low-level somatic mosaic mother: Genetic and functional studies. (September 2016) - Tsai, Meng-Han; Kuo, Pei-Wen; Myers, Candace T.; Li, Shih-Wen; Lin, Wei-Che; Fu, Ting-Ying; Chang, Hsin-Yun; Mefford, Heather C.; Chang, Yao-Chung; Tsai, Jin-Wu
Abstract: Purpose: To study the genetics and functional alteration of a family with X-linked lissencephaly and subcortical band heterotopia. Methods: Five affected patients (one male with lissencephaly, four female with subcortical band heterotopia) and their relatives were studied. Sanger sequencing of DCX gene, allele specific PCR and molecular inversion probe technique were performed. Mutant and wild type of the gene products, namely doublecortin, were expressed in cells followed by immunostaining to explore the localization of doublecortin and microtubules in cells. In vitro microtubule-binding protein spin-down assay was performed to quantify the binding ability of doublecortin to microtubules. Key findings: We identified a novel DCX mutation c.785A > G, p.Asp262Gly that segregated with the affected members of the family. Allele specific PCR and molecular inversion probe technique demonstrated that the asymptomatic female carrier had an 8% mutant allele fraction in DNA derived from peripheral leukocytes. This mother had 7 children, 4 of whom were affected and all four affected siblings carried the mutation. Functional study showed that the mutant doublecortin protein had a significant reduction of its ability to bind microtubules. Significance: Low level mosaicism could be a cause of inherited risk from asymptomatic parents for DCX related lissencephaly-subcortical band heterotopia spectrum. This is particularly important in terms of genetic counselling for recurrent risk of future pregnancies. The reduced binding affinity of mutant doublecortin may contribute to developmental malformation of the cerebral cortex. Highlights: A novel DCX p.D262G mutation was identified in an unaffected mother with 8% mosaicism. Low level mosaicism in DCX could be a hidden risk of inheriting lissencephaly/SBH. The p.D262G mutant doublecortin has reduced binding affinity to microtubules.